2012
DOI: 10.3233/bme-2012-0697
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose nanowhiskers: Preparation, characterization and cytotoxicity evaluation

Abstract: Objective: To characterize the structure and to evaluate the cytotoxicity of cellulose nanowhiskers (CNW) prepared from cotton linters.Methods: A series of CNW dispersions was prepared by hydrolyzing cotton linters with sulfuric acid. The structure of CNW was characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FT-IR) and X-ray diffraction (XRD). The cytotoxicity of CNW dispersions to L929 cells was preliminarily investigated by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 15 publications
1
30
0
Order By: Relevance
“…This needs to be considered as it is well established that nanoparticle size, shape, and morphology may influence toxicity (Hanif et al, 2014). Currently, no published results have revealed definite safety concerns of NC in the workplace, but indications of dose-dependent toxicity and inflammatory effects have been reported (Ni et al, 2012;Pereira et al, 2013). Therefore, it is imperative to thoroughly assess and understand the impact of NC on human health and the environment.…”
Section: Discussionmentioning
confidence: 99%
“…This needs to be considered as it is well established that nanoparticle size, shape, and morphology may influence toxicity (Hanif et al, 2014). Currently, no published results have revealed definite safety concerns of NC in the workplace, but indications of dose-dependent toxicity and inflammatory effects have been reported (Ni et al, 2012;Pereira et al, 2013). Therefore, it is imperative to thoroughly assess and understand the impact of NC on human health and the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Dong, Hirani, Colacino, Lee, and Roman (2012) reported no cytotoxic effect of plant-derived CNCs for a variety of mammalian cells in the concentration range of 0-0.05 mg/mL, up to 48 h. Other authors observed a dosedependent cytotoxicity of CNCs. As an example, Ni et al (2012) reported the cytotoxicity of CNCs prepared from cotton linters, presented as cellulose nanowhiskers. Low cytotoxicity was observed at low concentrations (up to 2.0 mg/mL), increasing for higher concentrations (10 mg/mL).…”
Section: Cytotoxicitymentioning
confidence: 99%
“…28,29 For example, Endes et al 30 did not detect any signicant cytotoxicity or oxidative stress induction or (pro)inammatory responses in a multi-cellular in vitro test of the human epithelial airway barrier at the air-liquid interface for CNC suspensions with different concentrations, even up to the highest concentration of 1.57 mg cm À3 . Ni et al 31 investigated the cytotoxicity of CNC dispersions to L929 cells by MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay and found no signicant effect of different suspension concentrations ranging from 0.01% to 0.2%. Hanif et al 32 also shared a similar result in which they showed that the CNC do not reveal much cytotoxicity at various concentrations up to 250 mg ml À1 .…”
Section: Introductionmentioning
confidence: 99%